Numerical Simulations of Dam-break Floods with MPM. (2017) - Zhao, Xuanyu; Liang, Dongfang; Martinelli, Mario
Abstract: Due to the ability to model large deformations and the ease of dealing with boundary conditions in a Lagrangian framework, the material point method is getting more popularity in geotechnical engineering applications. In this paper, the material point is tentatively applied to model problems of hydrodynamics as an introduction to this field. Dam-break flows with different initial aspect ratios are simulated in both the material point method and an extensively verified shallow water equations model. In order to test the accuracy and stability of the material point method, simulations of dam-break flows are carried out and the results are in good agreement with other validated numerical methods and experimental data. From the comparisons between the simulations in both the material point method and shallow water equations model, a critical aspect ratio value for the applicability of the shallow water equations is found to be 1. The material point method shows its potential to tackle hydrodynamics related problems.